Copepod functional traits and groups show divergent biogeographies in the global ocean. (19th October 2022) - Benedetti, Fabio; Wydler, Jonas; Vogt, Meike
Abstract: Aim: The distribution of zooplankton functional traits is a key factor for regulating food web dynamics and carbon cycling in the oceans. Yet, we lack a clear understanding of how many functional groups (FGs) exist in the zooplankton and how their traits are distributed on a global scale. Here, we model and map the environmental habitats of copepod (i.e. the main component of marine zooplankton) FGs to identify regions sharing similar functional trait expression at the community level. Taxon: Marine planktonic Neocopepoda. Location: Global ocean. Methods: Factor analysis on mixed data and hierarchical clustering were used to identify copepod FGs based on five species‐level functional traits. An ensemble of species distribution models was used to estimate the environmental niches of the species modelled and the community weighted mean (CWM) values of the traits studied. Ocean regions were defined based on their community‐level mean trait expression using principal component analysis and hierarchical clustering. Results: Eleven global copepods FGs were identified. They displayed contrasting latitudinal patterns in mean annual habitat suitability that could be explained by differences in environmental niche preferences: two FGs were associated with polar conditions, one followed the global temperature gradient, five were associated with tropical oligotrophic gyres and the remaining three with boundary currents and counter currents. Four main regions of varying CWM trait values emerged: the Southern Ocean, the northern and southern high latitudes, the tropical gyres and the boundary currents and upwelling systems. Conclusions: The present FGs will improve the representation of copepods in global marine ecosystem models. This study improves the understanding of the patterns and drivers of copepods trait biogeography and will serve as a basis for studying links between zooplankton biodiversity and ecosystem functioning in a context of climate change.